Design and Implementation of 2x4 Element Hexagonal Array Microstrip Antenna with DGS Method in the Shape of Dumbbell Circle Head for 2.4 GHz Frequency Wi-Fi Applications - Koesmarijanto Koesmarijanto; Nur Afifah Putri Alifia; Hendro Darmono (Jurnal Jaringan Telekomunikasi, 2022)
This study discusses the design and manufacture of microstrip antennas that aim to widen the bandwidth in the application of Wi-Fi in the form of a hexagonal patch composed of a 2x4 element array. Microstrip antennas have a weakness, namely narrow bandwidth, therefore a modification is needed using the DGS (Defected Ground Structure) method in the form of a dumbbell circle head. The allocation of the Wi-Fi working frequency that is often used in the community is 2.4 GHz in accordance with the IEEE 802.11 protocol standard. This study discusses the result and the effect of the performance of an 2x4-element microstrip array antenna using DGS. This DGS is placed on the ground plane and uses a PCB with an epoxy fiberglass substrate material which has a dielectric constant of 4.58. The result of this research is an external device, namely a microstrip antenna that can increase data transfer capacity and work on a Wi-Fi frequency of 2.4 GHz. This research is in accordance with the antenna test parameters, which have a return loss value of -22.7 dB and VSWR 1.15. 1. The results of testing the bandwidth of the hexagonal 2x4 element microstrip patch antenna with a defected ground structure of 34 MHz. The radiation pattern of the hexagonal 2x4 element microstrip patch antenna using DGS is directional. The results of the power level implementation of a hexagonal microstrip patch antenna arranged in a 2x4 array using a DGS dBm can increase power level by 7 dBm.